2009
DOI: 10.1111/j.1365-2834.2009.00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions: managing the risk

Abstract: The transition to electronic records needs to be carefully managed to ensure that information on adverse drug reactions is included. The West Wales Adverse Drug Reaction profile, version II, is one strategy to achieve this in mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Further, the implementation of proactive medication monitoring in clinical practice, such as the West Wales Adverse Drug Reaction Profile, could be an important approach in identifying the potential ADRs associated with commonly prescribed medications (Jordan et al . , Gabe & Jordan , Gabe et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the implementation of proactive medication monitoring in clinical practice, such as the West Wales Adverse Drug Reaction Profile, could be an important approach in identifying the potential ADRs associated with commonly prescribed medications (Jordan et al . , Gabe & Jordan , Gabe et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Systematic approaches to medication monitoring ensure full collection of ADR data (Jordan et al . ), while minimizing the burden upon service users and clinicians of spontaneously recognizing, identifying and reporting potential problems with medication (Winterstein et al . , Kanjanarat et al .…”
Section: Introductionmentioning
confidence: 99%
“…In the psychiatric setting research has shown that the implementation of evaluation checklists is associated with an increased detection and actioning of adverse drug effects associated with antipsychotic medication by nurses 17 , 18. By dissecting out those factors as to why our patient developed neuropsychiatric symptoms, it helps formulate a checklist that can prompt clinicians who both prescribe and administer the medication to consider patient risks factors to developing neuropsychiatric sequelae after commencing efavirenz (table 1); this could be accompanied by nurses recording all medication administered to ensure information is not overlooked on admission and consultant review 19…”
Section: Discussionmentioning
confidence: 99%